Evaluation of quality of life in women with endometriosis and management method with side effects of the disease - Łuczak-Wawrzyniak, Jadwiga; Szczepańska, Małgorzata; Skrzypczak, Jana (Menopause Review/Przegląd Menopauzalny, 2007)
Endometriosis, like many chronic diseases, makes women unable to fulfill their needs and destroys their sense of happiness. The quality of life is defined as a method and effectiveness in solving problems. Objective: The aim of the paper was to evaluate quality of life in women with endometriosis and the management method of side effects of the disease. Psychological scales were employed in our study. Material and methods: In our research we included 26 women admitted to the Division of Reproduction of the Medical University in Poznan with diagnosed endometriosis of the small pelvis. We analyzed individual predisposition, used strategies and their effectiveness in controlling endometriosis side effects and transposition of obtained results into particular life zones: physical, psychological, interpersonal and somatic, as a quality of life markers. Results: Among women with endometriosis there were was no progression in depression symptoms. They however presented high level of quality of life. They used the following strategies for pain control: (prayers, searching for hope, and declaration of dealing with pain causing the situation). They muted rated anger and relations with family and their support rate positively. They accepted the disease on at a high level, which allowed them to prevent from a negative impact on psychosocial function. They had a high level of a sense of own effectiveness which built a self-confidence in a difficult and stressfull situation. Conclusions: In women with endometriosis there is no evidence of quality of life deterioration. Endometriosis stimulates natural resources, allowing women to fulfill various goals despite of chronic disease. Women with endometriosis get used to their disease, keeping a good relationship with close coworkers colleagues and fulfilling their life’s goals while having at the same time a high level of self-satisfaction.